2013
DOI: 10.1364/oe.21.030999
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and reception of Quad-Carrier QPSK-OFDM signal with blind equalization and overhead-free operation

Abstract: . (2013). Transmission and reception of quad-carrier QPSK-OFDM signal with blind equalization and overhead-free operation. Optics Express, 21(25), 30999-31005. DOI: 10.1364/OE.21.030999 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Frequency domain equalization (FDE) is simple and effective, but it needs overheads (TSs and pilot tones) during equalization which leads to the SE degradation. Few subcarriers OFDM (dual-subcarrier and quad-subcarrier) transmission and reception was proposed in our previous work [10,11] to avoid overhead during equalization. Compared to conventional OFDM with a large number of subcarriers, an unbeatable advantage of OFDM with a small number of subcarriers is that the peak-toaverage power ratio (PAPR) is quite low [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency domain equalization (FDE) is simple and effective, but it needs overheads (TSs and pilot tones) during equalization which leads to the SE degradation. Few subcarriers OFDM (dual-subcarrier and quad-subcarrier) transmission and reception was proposed in our previous work [10,11] to avoid overhead during equalization. Compared to conventional OFDM with a large number of subcarriers, an unbeatable advantage of OFDM with a small number of subcarriers is that the peak-toaverage power ratio (PAPR) is quite low [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the SE is significantly reduced as the pilot tones should be inserted in every OFDM symbol with few subcarriers. Fortunately, we found that the Quadrature Phase Shift Keyed (QPSK) OFDM signal with dual-subcarrier and quad-subcarrier are 9QAM [10] and 25QAM [11] in the time domain, respectively. With these special properties, QPSK-OFDM signal with dual-subcarrier and quad-subcarrier can be equalized in the time domain with cascaded multimodulus algorithm (CMMA) equalization method.…”
Section: Introductionmentioning
confidence: 99%